The Concept of Understand and Knowledge of al-Qushayri | المعرفة والبحث عن اليقين عند عبد الكريم القشيري - Abdul Hayy Al-Kattani (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2016)
Everyone should undesrtand the knowledge or science, for getting the perfection of himself and goodwill, straightening his behavior, and because God honor and prise him, and promise a great reward, and if science requirement of every human being, especially intellectuals and scholars, do not mean to learning whatever would or ever, but they should priority conviction science, it means conviction in science should be the porpouse of scholar looking for the right, and take the path or approach that give him a ride to achieve this porpouse. This article talks about the concept of understand and knowledge of al-Qushayri who is the big scholar of Islam.